2008
DOI: 10.1177/00333549081230s207
|View full text |Cite
|
Sign up to set email alerts
|

Service Learning within the University of Connecticut Master of Public Health Program

Abstract: SYNOPSISSince 2005, the University of Connecticut Master of Public Health Program has administered its required service-learning practicum through coordinated activities of second-year students assigned to examine a pressing public health issue in Connecticut. The initiative underscores our program's commitment to preparing students for careers as leaders in applied practice and our emphasis on collaboration. Our thematic approach links content across the core curriculum, provides a venue where students demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…There are examples in the fields of public administration (Bushouse and Morrison 2001;Dicke, Dowden, and Torres 2004;Lambright and Lu 2009;Reinke 2003), social work (Rocha 2000;Wells 2006), nursing (Baker et al 2004), physical therapy (Reynolds 2005;Beling 2004), public health (Gregorio, DeChello, and Segal 2008), and occupational therapy (Beck and Barnes 2007). According to Barbara Jacoby (1996, 5), "service learning is a form of experiential education in which students engage in activities that address human and community needs together with structured opportunities intentionally designed to promote student learning and development."…”
mentioning
confidence: 99%
“…There are examples in the fields of public administration (Bushouse and Morrison 2001;Dicke, Dowden, and Torres 2004;Lambright and Lu 2009;Reinke 2003), social work (Rocha 2000;Wells 2006), nursing (Baker et al 2004), physical therapy (Reynolds 2005;Beling 2004), public health (Gregorio, DeChello, and Segal 2008), and occupational therapy (Beck and Barnes 2007). According to Barbara Jacoby (1996, 5), "service learning is a form of experiential education in which students engage in activities that address human and community needs together with structured opportunities intentionally designed to promote student learning and development."…”
mentioning
confidence: 99%
“…Service learning has been conducted in other MPH programs. For example, Gregorio, DeChello, & Segal (2008) evaluated three MPH service learning experiences at the University of Connecticut and found that 68% of students derived high or very high educational value from the experience. Hou (2009) from the University of Georgia described her experience with service learning in a first-year MPH course and found that students derived benefits from engaging with community members, working as a team in a realistic setting, and applying their knowledge in a concrete manner.…”
Section: Discussionmentioning
confidence: 99%
“…Public health programs rely on learning by doing to teach various topics and skills (Gregorio, DeChello, & Segal, 2008). Experiential learning involves gaining classroom knowledge and skills and applying what is learned inside the classroom in a real-world setting with immediate consequences outside the classroom (Bentley & Swan, 2018; Cashman & Seifer, 2008).…”
Section: Public Health Policy Through Experiential and Service Learningmentioning
confidence: 99%